BOOK REVIEW OF YANN MARTEL’S LIFE OF PI - Titisari, Kurnia (LANTERN (Journal on English Language, Culture and Literature), 2014)
Humans are considered as the most perfect creatures physiologically and psychologically to survive and socialize with one another. However, sometimes people do not realize that there is an enormous power that governs the universe and everything in it. How the planets rotate in the solar system around the sun; how the seasons change; and how everything happens perfectly are the evidences that show the power beyond humans’control. From this evolves the belief in God as the creator and controller of the universe. When people are able to do something, they tend not to feel the intervention of God in their work and forget to be grateful, but when people feel powerless or are approaching death, then they feel the force beyond their control of this life, which is God. Besides humans also want answers to the questions that are beyond their intellectual reach. Obviously science can not provide answers. Because everything comes from God, only God knows the absolute truth. Such understanding leads to something that people call religion. That is why humans really need religion to satisfy their spiritual thirst and to meet the spiritual needs of human beings.Basically all religions are the same. They teach people to believe in God. All of them teach kindness and respect to parents and fellow human beings. They suggest to give charity and not steal or fornicate. Religions lead their followers to walk in the right way. Religion with the most followers include Islam, Christianity, Catholicism, Hinduism and Buddhism. A person usually embraces only one religion and is supposed to be like that. The said religion is usually  attached to the person since he was born. However every person has the right to decide for himself which religion he wants to believe. Through a religion, a person tries to understand the meaning of life and what is happening in his life.Literary works can offer the best representation of life, and a novel is one kind of literary works that is closest to the public because the storyline is not far from the reality of people's lives. A novel can also give a moral message with intangible religious values, including the belief in God. One of the novels that tell the power of God in human’s life is Yann Martel’s Life of Pi. This novel is about a young Indian boy, Piscine Molitor Patel (Pi) who is in search of a belief to follow in life. Confusion causes Pi to try to embrace all the new religions he recently knows and alternately believes to be right. His confusion about religions is still going on until he is adult. This novel tells not only about religion but also about human’s trust in God. These things lead to the conflicts in this story and make the novel interesting to examine more deeply.